An improved clinical model to predict stimulated C‐peptide in children with recent‐onset type 1 diabetes. Issue 2 (8th January 2019) - Buchanan, Kerry; Mehdi, Ahmed M; Hughes, Ian; Cotterill, Andrew; Le Cao, Kim‐Anh; Thomas, Ranjeny; Harris, Mark
Abstract : Background: Stimulated C‐peptide measurement after a mixed meal tolerance test (MMTT) is the accepted gold standard for assessing residual beta‐cell function in type 1 diabetes (T1D); however, this approach is impractical outside of clinical trials. Objective: To develop an improved estimate of residual beta‐cell function in children with T1D using commonly measured clinical variables. Subjects/Methods: A clinical model to predict 90‐minute MMTT stimulated C‐peptide in children with recent‐onset T1D was developed from the combined AbATE, START, and TIDAL placebo subjects (n = 46) 6 months post‐recruitment using multiple linear regression. This model was then validated in a clinical cohort (Hvidoere study group, n = 262). Results: A model of estimated C‐peptide at 6 months post‐diagnosis, which included age, gender, body mass index (BMI), hemoglobin A1c (HbA1c), and insulin dose predicted 90‐minute stimulated C‐peptide measurements (adjusted R 2  = 0.63, P  < 0.0001). The predictive value of insulin dose and HbA1c alone (IDAA1c) for 90‐minute stimulated C‐peptide was significantly lower ( R 2 = 0.37, P  < 0.0001). The slopes of linear regression lines of the estimated and stimulated 90‐minute C‐peptide levels obtained at 6 and 12 months post diagnosis in the Hvidoere clinical cohort were R 2  = 0.36, P  < 0.0001 at 6 months and R 2  = 0.37, P < 0.0001 at 12 months. Conclusions: A clinical model including age, gender, BMI, HbA1c, and insulin dose predicts stimulated C‐peptide levels in children with recent‐onset T1D. Estimated C‐peptide is an improved surrogate to monitor residual beta‐cell function outside clinical trial settings.